Web-based Exploration of Results From a Large European Survey on Dictionary Use and Culture: ESDexplorer - Wolfer, Sascha; Kosem, Iztok; Lew, Robert; Müller-Spitzer, Carolin; Ribeiro Silveira, Maria (Lexikos, 2018)
We present ESDexplorer (https://owid.shinyapps.io/ESDexplorer), a browser application which allows the user to explore the data from a large European survey on dictionary use and culture. We built ESDexplorer with several target groups in mind: our cooperation partners, other researchers, and a more general public interested in the results. Also, we present in detail the architecture and technological realisation of the application and discuss some legal aspects of data protection that motivated some architectural choices.